Mental health symptoms in children and adolescents during COVID-19 in Australia. (February 2023) - Sicouri, Gemma; March, Sonja; Pellicano, Elizabeth; De Young, Alex C; Donovan, Caroline L; Cobham, Vanessa E; Rowe, Arlen; Brett, Simon; Russell, Jeremy K; Uhlmann, Laura; Hudson, Jennifer L
Objective: COVID-19 has led to disruptions to the lives of Australian families through social distancing, school closures, a temporary move to home-based online learning, and effective lockdown. Understanding the effects on child and adolescent mental health is important to inform policies to support communities as they continue to face the pandemic and future crises. This paper sought to report on mental health symptoms in Australian children and adolescents during the initial stages of the pandemic (May to November 2020) and to examine their association with child/family characteristics and exposure to the broad COVID-19 environment. Methods: An online baseline survey was completed by 1327 parents and carers of Australian children aged 4 to 17 years. Parents/carers reported on their child's mental health using five measures, including emotional symptoms, conduct problems, hyperactivity/inattention, anxiety symptoms and depressive symptoms. Child/family characteristics and COVID-related variables were measured. Results: Overall, 30.5%, 26.3% and 9.5% of our sample scored in the high to very high range for emotional symptoms, conduct problems and hyperactivity/inattention, respectively. Similarly, 20.2% and 20.4% of our sample scored in the clinical range for anxiety symptoms and depressive symptoms, respectively. A child's pre-existing mental health diagnosis, neurodevelopmental condition and chronic illness significantly predicted parent-reported child and adolescent mental health symptoms. Parental mental health symptoms, having a close contact with COVID-19 and applying for government financial assistance during COVID-19, were significantly associated with child and adolescent mental health symptoms. Conclusion: Our findings show that Australian children and adolescents experienced considerable levels of mental health symptoms during the initial phase of COVID-19. This highlights the need for targeted and effective support for affected youth, particularly for those with pre-existing vulnerabilities.